2010
DOI: 10.1002/adfm.201001203
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Piezoelectric Power Generation of ZnO Nanowire Arrays Grown by Different Methods

Abstract: The piezoelectric power generation from ZnO nanowire arrays grown on different substrates using different methods is investigated. ZnO nanowires were grown on n‐SiC and n‐Si substrates using both the high‐temperature vapor liquid solid (VLS) and the low‐temperature aqueous chemical growth (ACG) methods. A conductive atomic force microscope (AFM) is used in contact mode to deflect the ZnO nanowire arrays. No substrate effect was observed but the growth method, crystal quality, density, length, and diameter (asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 29 publications
6
78
0
Order By: Relevance
“…While the average lengths of the NRs for common paper, flexible plastic, textile fabric and aluminum foil are ~1-1.2 μm, ~2 μm, ~1.5 μm and ~2-2.4 μm, respectively, as shown in Figure 2(a-d). It is already reported that the performance of the nanogenerators was not dependent on the substrates but mainly depended on the crystal quality, effective length, diameter and density of the nanowires across the substrate (Riaz et al 2011). In our case, the aspect ratio and the density of the ZnO nanorods (NRs) have influenced the recorded output signals in consistence with other reports (Wang and Song 2006).…”
Section: Resultsmentioning
confidence: 98%
“…While the average lengths of the NRs for common paper, flexible plastic, textile fabric and aluminum foil are ~1-1.2 μm, ~2 μm, ~1.5 μm and ~2-2.4 μm, respectively, as shown in Figure 2(a-d). It is already reported that the performance of the nanogenerators was not dependent on the substrates but mainly depended on the crystal quality, effective length, diameter and density of the nanowires across the substrate (Riaz et al 2011). In our case, the aspect ratio and the density of the ZnO nanorods (NRs) have influenced the recorded output signals in consistence with other reports (Wang and Song 2006).…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, Riaz et al [20] studied the electrical potential vs. the aspect ratio of different nanowires at a fixed length of 1000 nm and varied diameters. It is found the output electrical potential increases with decreasing in diameter of the nanowires and saturated at a diameter below 12.5 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, various experimental studies have probed either the electrical [15,16] or mechanical [17][18][19] behavior of nanowires separately. Riaz et al [20] experimentally and initially studied electrical potential-related size effects of ZnO nanowire using both the high-temperature vaporliquid-solid (VLS) and the low-temperature aqueous chemical growth (ACG) methods. They also theoretically investigated relationship between aspect ratio and density of the nanowire and resulted electrical potential output.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…caused by an externally applied pressure, thin NWs (few nm thick) offer a large surface-to-volume ratio, making them interesting for surface and bending sensitive applications. 9 Closely packed NWs with uniform spacing can improve light trapping and charge separation in nanowire-polymer solar cells. 10,11 By using tilted NWs and NNs, the field emission characteristic is controllable.…”
Section: © 2016 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%